Construction of Integer Operations of the Gasing-Mathematics Method from the Perspective of APOS Theory - Evy Lalan Langi; Marilyn Lasarus Kondolayuk; Katriani Dea Domassang (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
A low mastery of integer operations remains a significant cause of students’ weak mathematical literacy, as current teaching methods often emphasize mechanical computation over conceptual understanding. This study aims to describe how students construct their understanding of integer operations through the Gasing Method from the perspective of APOS Theory. This research employed a descriptive qualitative design with a task-based case study approach, involving three mathematics education students who had participated in Gasing training and obtained the highest scores on an integer operation test. Data were collected through written tasks and semi-structured interviews, then analyzed using the stages of APOS thinking: Action, Process, Object, and Schema, through iterative coding and triangulation. The results show that the Gasing Method supports the progression of students’ thinking from procedural to conceptual: the Action stage appears in step-by-step computation, the Process stage in mental prediction and verbal explanation, the Object stage in recognizing relationships among operations, and the Schema stage in integrating these into a coherent conceptual framework. The study concludes that the integration of Gasing and APOS provides a powerful pedagogical model that bridges concrete and abstract reasoning, offering meaningful implications for mathematics teachers in designing culturally grounded yet cognitively informed numeracy learning.